Cash Receipt and Expenditure Application Based on a Website Using PHP at PT Indika Teknologi Perkasa - Fitria; Ahmad Baihaqy; Emy Iryanie (MultiTech Publisher, 2024)
PT Indika Teknologi Perkasa still uses manual cash receipt and expenditure recording with Microsoft Excel, which is at risk of causing errors and data loss. This research aims to develop a web-based application using PHP and MySQL, in order to improve efficiency and security in the management of the company's cash. The research method used is qualitative with a case study approach through interviews, observations, and documentation. The research results show that the developed application successfully automated cash transaction recording, provided real-time reports, and enhanced the security of financial data. In conclusion, this application improves the efficiency of cash recording at PT Indika Teknologi Perkasa. Suggestions for further development include the addition of integration features and automatic backup